TRADE-OFF BETWEEN LIQUIDITY AND PROFITABILITY: CASE STUDY OF SUN PHARMACEUTICAL INDUSTRIES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study is carried out to investigate the  trade-off between liquidity and profitability. The  main motive any business firm is to earn profit  and for earning profit they need to manage their  assets properly. The firm should be ready with  its asset that are liquid to meet its short term  i.e. current liabilities. Effective working capital  management should be employed by the business  firms to ensure trade-off between liquidity and  profitability. The management of the business  firm is naturally keen to measure its operating  efficiency. Similarly the owners invest their funds  in the expectation of reasonable returns. Sun  Pharmaceutical Industries Ltd. is the fifth largest  specialty generic pharmaceutical company in  the world, which was incorporated in the year  1983. The Company has global presence with  41 manufacturing facilities across the world.  India and the US are two predominant markets  accounting for nearly 70% of the company’s  revenue. The data was collected through  secondary source i.e. audited financial statement  for the 10 years from 2010-2011 to 2019- 20. The data analyzed by using several ratios  related with liquidity and profitability, also used  descriptive statistics, Correlation coefficient and  liner multi regression analysis. The association  of ROI, ROE and NPR with APP, CR and  CA to TA is statistically significant and ROI,  ROE and NPR are negatively correlated with  ARP, ICP, CCC, CA to TA, GWCTR. Sun  Pharmaceutical Industries Ltd. is taking benefit  of extensive credit period allowed by their  suppliers. However they should have stability in  the decisions concerning management of current  assets and liabilities.
Keywords: Liquidity; Profitability; relationship; trade-off; current assets; current liabilities